2020
DOI: 10.20944/preprints202001.0261.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The n-10 Fatty Acids Family in the Lipidome of Human Prostatic Adenocarcinoma Cell Membranes and Extracellular Vesicles

Abstract: A new pathway leading to the n-10 fatty acid series has been recently evidenced, starting from sapienic acid - a monounsaturated fatty acid (MUFA) resulting from the transformation of palmitic acid by delta-6 desaturase. Sapienic acid attracts attention as novel marker of cancer cell plasticity. Here, we analyzed fatty acids including the n-10 fatty acid contents, and compared for the first time cell membranes and the corresponding extracellular vesicles (EV) of two human prostatic adenocarcinoma cell lines of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 47 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…86 extraordinary finding, another research group showed that two human prostatic adenocarcinoma cell lines of different aggressiveness preferentially synthesized sapienic acid. 87 The researchers found that sapienic acid and its C18 elongated product at 6-8% and 3-6% (wt/wt of total fatty acids), respectively. As a result, sapienic acid has become a spotlight in the cancer research field, providing insights into the developmental mechanisms of cancer cells and a breakthrough point for biomarker discovery in the prognosis of various diseases.…”
Section: Shift Of Fatty Acid Pathways In Cancer Cellsmentioning
confidence: 99%
“…86 extraordinary finding, another research group showed that two human prostatic adenocarcinoma cell lines of different aggressiveness preferentially synthesized sapienic acid. 87 The researchers found that sapienic acid and its C18 elongated product at 6-8% and 3-6% (wt/wt of total fatty acids), respectively. As a result, sapienic acid has become a spotlight in the cancer research field, providing insights into the developmental mechanisms of cancer cells and a breakthrough point for biomarker discovery in the prognosis of various diseases.…”
Section: Shift Of Fatty Acid Pathways In Cancer Cellsmentioning
confidence: 99%